In Silico Analysis of CD40 Mutations and Their Implications for Quinoline-benzoic acid derivatives Based Therapy in Graves' Disease - Yunaini, Luluk; Kristanty, Diyah; Sari, Puji; Dwira, Surya; Suryandari, Dwi Anita; Bustami, Arleni (Indonesian Journal of Medical Chemistry and Bioinformatics, 2025)
Graves' disease is an autoimmune disorder in which the CD40-CD154 interaction plays a critical role in T-cell activation. In this study, in silico methods were employed to analyze the binding interactions of quinoline-benzoic acid derivatives (NSB, FSB, and NQB) with the CD40 receptor and to investigate the implications of specific CD40 mutations for drug efficacy. In this reseach conducted by molecular simulation approach with molecular docking Results Mutation analysis of CD40 identified alterations in key residues, such as R203C, which may impact ligand-independent activation and downstream TRAF binding, crucial for signal transduction. These findings highlight the therapeutic potential of quinoline-benzoic acid derivatives for targeting CD40 in Graves' disease, particularly in the context of receptor mutations. The integration of molecular docking, mutation analysis, and pharmacokinetic profiling provides a comprehensive framework for designing effective CD40-targeted therapies.